Does a "super-presidential republic" exist? The phenomenon of super-presidency experienced by post-communist countries of Eastern Europe and Asia - Roman Martyniuk; Oleksii Datsiuk; Mykola Romanov; Yurii Irkha (Eastern Journal of European Studies)
The aim of the work is to prove the scientific fallacy of the notion of a "super-presidential republic" as a form of government. In countries where the power of the president does not meet the necessary opposition from civil society and other state authorities, that power is transformed into the phenomenon of super-presidency. The desire to understand the essence of this phenomenon has led to the emergence in the professional community, primarily among political scientists of the post-communist countries of Eastern Europe and Asia, of the terms "super-presidential regime" and "super-presidential republic" or "super-presidentialism". The use of the latter two terms reflects an attempt by a certain circle of scientists to explain the phenomenon of super-presidency as a form of government. Here lies a serious methodological error, since a "super-presidential republic" is not a form of government. If democratic political institutions are weak and civil society is underdeveloped, any republic in which the constitutional status of the president ensures his dominant influence over the executive branch can become "super-presidential".